High secondary attack rate and persistence of SARS-CoV-2 antibodies in household transmission study participants, Finland 2020–2021 - Dub, Timothée; Solastie, Anna; Hagberg, Lotta; Liedes, Oona; Nohynek, Hanna; Haveri, Anu; Virta, Camilla; Vara, Saimi; Lasander, Mervi; Ekström, Nina; Österlund, Pamela; Lind, Katja; et al. (Frontiers in Medicine, 2022)
Background. Household transmission studies offer the opportunity to assess both secondary attack rate (SAR) and persistence of SARS-CoV-2 antibodies over time. Methods. In Spring 2020, we invited confirmed COVID-19 cases and their household members to four visits, where we collected nasopharyngeal and serum samples over 28 days after index case onset. We calculated SAR based on the presence of SARS-CoV-2 neutralizing antibodies (NAb) and assessed the persistence of NAb and IgG antibodies (Ab) against SARS-CoV-2 spike glycoprotein and nucleoprotein. Results. SAR was 45% (39/87), including 35 symptomatic secondary cases. During the initial 28-day follow-up, 62% (80/129) of participants developed NAb. Of those that seroconverted, 90% (63/70), 85% (63/74) and 78% (45/58) still had NAb to early B-lineage SARS-CoV-2 three, six and twelve months after the onset of the index case. Anti-spike IgG Ab persisted in 100% (69/69), 97% (72/74) and 93% (55/59) of seroconverted participants after three, six and twelve months, while anti-nucleoprotein IgG Ab levels waned faster, persisting in 99% (68/69), 78% (58/74) and 55% (39/71) of participants, respectively. Conclusions. Following detection of a COVID-19 case in a household, other members had a high risk of becoming infected. NAb to early B-lineage SARS-CoV-2 persisted for at least a year in most cases.